2015
DOI: 10.1515/arsm-2015-0025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tumor angiogenesis in patients with non-small cell lung carcinoma

Abstract: The aim of this study is to evaluate tumor angiogenesis in patients with non-small cell lung carcinoma. A total of 20 patients with pulmonary adenocarinoma have been included in the study. In order to evaluate tumor angiogenesis we studied the importance of CD34 expression. Evaluation of vascular density was performed with a semiautomated method using the dedicated software called ImageJ. We introduced in our study 20 patients with lung adenocarcinoma. We were able to identify tumor angiogenesis in 19 cases (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Tumor proliferative activity is usually assessed by Ki-67. CD31 is expressed on blood vascular endothelial cells and is considered as a marker of endothelial proliferation in patients with NSCLC (Suciu et al., 2015 ). Circulating microvascular density of the tumor has been established as prognostic factors in many studies (Nefedova et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor proliferative activity is usually assessed by Ki-67. CD31 is expressed on blood vascular endothelial cells and is considered as a marker of endothelial proliferation in patients with NSCLC (Suciu et al., 2015 ). Circulating microvascular density of the tumor has been established as prognostic factors in many studies (Nefedova et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike genetic markers, determining serum levels of neutrophils, platelets and lymphocytes are routine tests that are performed in all of these patients and do not involve increased financial costs [15]. Also, it is well known the fact that the inflamation play an important role in the healing process [16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…There are also authors in the literature who have shown the expansion of cystic veins in patients who had mesocaval shunts, in these cases cystic veins function as collateral drainage pathways [6]. Thus, cholecystic varicose veins are observed in 34% of patients with extrahepatic portal venous obstruction [7][8][9].…”
Section: Resultsmentioning
confidence: 99%